Lady and the Trump: Status and Wealth in the Marriage Market - Johan Almenberg; Anna Dreber (Research Institute of Industrial Economics (IFN), 2008)
We examine a hitherto unexplored aspect of intergenerational transmission of economic standing, namely culturally determined status markers and their valuation in the marriage market. We take nobility to be such a status marker. We propose a two-trait extension of the optimal sorting model in Becker (1973). Using data on Swedish marriages we test the hypothesis that nobility have a greater probability of marrying up in terms of wealth. Our main finding is a sizeable and statistically significant positive effect for nobility. We use unique data on the evolution of nobility to make some predictions about the longevity of this institution.
Keywords: D13; D20; J11; J12; 330; Marriage; Status; Intergenerational Transmission; Nobility; Ehe; Sozialer Status; Adel; Vermögen; Intergenerationale Übertragung; Schweden